The Convergence of Crowd Funding and Zakat System in India: An Integrated Approach for Human Welfare - Muhammed Ashiq; Ubaid Mushtaq (Universitas Ahmad Dahlan, 2020)
The impact of the Zakat system on human welfare is well established. In India, there is a significant development in terms of localised management of zakat system. However, the targeted delivery of zakat funds, unorganised collections and lack of transparency remain a matter of concern. There is no formal institutional mechanism for efficient Zakat distribution, and problems of circularity are at mostly affecting the progress of welfare mechanisms. Problems of circularity of Zakat funds are still, largely, incoherent and practically disconnected with the mechanics of philanthropic institutions. In our theoretical model, crowdfunding for welfare scheme is being treated as the determinant, which could mediate and alter the performance of zakat welfare. Further, make it more accessible and catering to more comprehensive economic benefits for the community. In this exploratory theoretical paper, we also examine the nature of a common platform for the Zakat distribution. In addition to this, how it could reduce the scrutiny of Government intervention and proper channelisation of Islamic philanthropic activities.Â Â